Impact of Open Government on Municipal Management Effectiveness: A study in the San Martin Region, Peru - Mabel , Contreras-Julian Rosa; Manuel , Delgado-Bardales Jose; Keller , Sanchez-Davila; Pilar , Palomino-Alvarado Gabriela del; Antonio , Perez-Arboleda Pedro; Alberto, Aparicio-Ballena, Jorge (Journal of Ecohumanism, 2024)
The main objective of the research was to determine the relationship between open government and the effectiveness of municipal management in the region of San Martín (Peru). It is basic research because it sought to expand knowledge of the two variables, with a quantitative approach because it sought to demonstrate whether there is a relationship, a non-experimental design because the variables were not manipulated, descriptive correlational and cross-sectional because the instruments were applied at a single point in time. The population consisted of 926,000 citizens between 23 and 65 years of age who have had the experience of using the services of provincial municipalities and who, therefore, can offer a better criterion for evaluating open government and the effectiveness of municipal management. The sample consisted of 1537 people. The technique used was the survey, and two questionnaires were used as instruments, one for each variable, which made it possible to collect information from the ten provincial municipalities in the region. The results obtained were that the degree of open government was fair with 67% and the degree of effectiveness of municipal management was fair with 68%. It was concluded that there is a high and significant positive relationship between open government and municipal management effectiveness, as Spearman's Rho was 0.824 (high positive correlation) and a p-value equal to 0.000 (p-value ≤ 0.01). Furthermore, 74% of the variability between open government and municipal management effectiveness is due to other factors.